Continuous dialysis of mixture of inorganic acids - Palatý, Zdeněk; Bendová, Helena (Elsevier Science BV, 2017)
The simultaneous transport of sulphuric and phosphoric acids through a polymeric membrane was investigated at steady state in a two-compartment counter-current dialyzer. For this purpose, an anion exchange membrane Neosepta-AFN (Astom Corporation, Tokyo, Japan) was used. This transport was quantified by four membrane mass transfer coefficients which are dependent upon the concentrations of both acids in the feed. These coefficients were determined by a two-step procedure. In the first step, the basic differential equations describing the dependences of the volumetric liquid flow rates and acid concentrations on the length coordinate in the individual compartments were numerically integrated. In the second step, an objective function was minimised to ensure the best coincidence between the experimental and calculated data.
Kontinuální dialýza směsi anorganických kyselin
Keywords: Diffusion dialysis; Anion-exchange membrane; Sulphuric acid; Phosphoric acid; Continuous dialyzer; Difuzní dialýza; Aniontově-výměnná membrána; Kyselina sírová; Kyselina fosforečná; Kontinuální dialyzér